Akt acts as a switch for GPCR transactivation of the TGF‐β receptor type 1. (18th December 2021) - Mohamed, Raafat; Shajimoon, Aravindra; Afroz, Rizwana; Gabr, Mai; Thomas, Walter G.; Little, Peter J.; Kamato, Danielle
Abstract : Transforming growth factor (TGF)‐β signalling commences with the engagement of TGF‐β ligand to cell surface TGF‐β receptors (TGFBR) stimulating Smad2 carboxyl‐terminal phosphorylation (phospho‐Smad2C) and downstream biological responses. In several cell models, G protein‐coupled receptors (GPCRs) transactivate the TGF‐β receptors type‐1 (TGFBR1) leading to phospho‐Smad2C, however, we have recently published that in keratinocytes thrombin did not transactivate the TGFBR1. The bulk of TGFBRs reside in the cytosol and in response to protein kinase B (Akt phosphorylation) can translocate to the cell surface increasing the cell's responsiveness to TGF‐β. In this study, we investigate the role of Akt in GPCR transactivation of the TGFBR1. We demonstrate that angiotensin II and thrombin do not phosphorylate Smad2C in human vascular smooth muscle cells and in keratinocytes respectively. We used Akt agonist, SC79 to sensitise the cells to Akt and observed that Ang II and thrombin phosphorylate Smad2C via Akt/AS160‐dependent pathways. We show that SC79 rapidly translocates TGFBRs to the cell surface thus increasing the cell's response to the GPCR agonist. These findings highlight novel mechanistic insight for the role of Akt in GPCR transactivation of the TGFBR1. Abstract : Cell sensitisation to Akt drives cytosolic transforming growth factor‐β receptors (TGFBRs) to the cell surface. G protein coupled receptors (GPCRs) can signal via transactivation‐dependent mechanisms. The abundance of TGFBRs on the cell surface enhances GPCR transactivation of the TGF‐β receptors type‐1 to activate Smad‐dependent pathways.